HAK POLITIK PEREMPUAN DALAM ISLAM (Usaha Memahami Nash Secara Kontekstual) - Jumni Nelli (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2013)
There are two opposite opinions about the permissibility of women in politics. One opinion states that women should be at home, devoted to her husband, just have a domestic role, and should not be involved in politics. Another opinion states that women have the freedom to play, both inside and outside the home as well as in politics. This happens because they don’t understand the concept of women's rights that purely political, as well as in understanding the text verse Al-Qur`an is still gender bias. The differences of those opinions related to the differences in understanding the Islamic sources especially the verses of the Al-Qur`an about politics. This paper discusses political rights of women in Islam, so that people can understand and not considered taboo against women who were involved in politics. Based on the identification, classification, and analysis of the texts of the Al-Qur'an and hadith about politics, found that women in politics have the right according to Islam. Men and women are obliged to enjoining good and forbidding evil through several ways including the political media. Islam does not distinguish between men and women in individual rights and social rights especially political rights. However, it was noted that all rights must be placed within the limits of natural as women.